Peran Petugas Pengendali Organisme Pengganggu Tumbuhan dan Penyuluh Pertanian dalam Penerapan PHT Wereng Batang Coklat di Jawa Bagian Tengah - , Raden Roro Siti Astuti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study was aimed to assess the role of functional officers in the implementation of IPM policy and to identify factors causing Brown Plant Hopper (BPH) outbreak in the central part of Java. The respondents were pest observers, extension workers, related officials, and community members. The respondents were selected by simple random sampling in the regencies of Bantul, Sleman, Klaten and Magelang. The collected data were descriptively and path analyzed to illustrate the observed phenomenon. The results showed that the outbreak of BPH in central part of Java is an impact of poor IPM implementation by the stakeholders. It is influenced by the ineffectiveness of communication and lack of commitment to IPM principals. The tasks of pest observers and extension workers have not oriented towards the implementation of IPM in the community members, but it is still limited to efforts their duties as a functional officers. Most of the pest observers and extension workers have a high commitment in conducting their main duty and function as functional officers despite the constraints they faced. These constraints are the quality of pest observers